Paraprotein-related renal disease. (October 2019) - Rana, Ritika; Pinney, Jennifer H.; Lachmann, Helen J.
Abstract: Paraprotein-related renal disease represents a diverse group of rare diseases characterized by distinct renal injury caused by the direct or indirect effects of a nephrotoxic paraprotein secreted by a clone of B cells. Early diagnosis and use of rapidly effective chemotherapy agents have improved patient and renal outcomes for these disorders. Patients can present with proteinuric renal impairment or tubular dysfunction. Diagnosis is often challenging because of the wide range of disease manifestations, difficulties with detection of the pathogenic clone and the common finding of an incidental paraprotein in elderly individuals. A renal biopsy along with haematological work-up is required to link a paraprotein with kidney disease. Chemotherapy directed at the plasma cell clone can halt the production of the paraprotein, which can in turn benefit renal function.